2021
DOI: 10.1037/hum0000167
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural comparison of compassion: An in-depth analysis of cultural differences in compassion using the Compassion of Others’ Lives (COOL) Scale.

Abstract: The results from the Turkish participants were higher for alleviating suffering behavior than those from Latin America. Reasons behind these differences will be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Along these lines, the factor labelled “Distress from witnessing the care recipient suffering” corresponds to the first component related to the perceptions and acknowledgment of suffering in the other individual, whereas the factor “Motivation/disposition for helping” corresponds to the motivational component related to the evoked desire to help the individual who is suffering. Moreover, the two obtained factors are also coherent with the subscales of the Compassion of Others’ Lives Scale (COOL; Chang et al., 2014) aimed at assessing compassion in general samples and whose factorial structure has been validated in different socio‐cultural contexts (Chang et al., 2020). Although the first CCS factor corresponds to the “empathy” COOL subscale, which contains items assessing the ability to acknowledge suffering in others and being able to put themselves in their position, the Motivation/disposition for helping factor could correspond to the COOL factor “alleviate suffering”, which contain items regarding the efforts of the person aimed at helping others.…”
Section: Discussionmentioning
confidence: 69%
“…Along these lines, the factor labelled “Distress from witnessing the care recipient suffering” corresponds to the first component related to the perceptions and acknowledgment of suffering in the other individual, whereas the factor “Motivation/disposition for helping” corresponds to the motivational component related to the evoked desire to help the individual who is suffering. Moreover, the two obtained factors are also coherent with the subscales of the Compassion of Others’ Lives Scale (COOL; Chang et al., 2014) aimed at assessing compassion in general samples and whose factorial structure has been validated in different socio‐cultural contexts (Chang et al., 2020). Although the first CCS factor corresponds to the “empathy” COOL subscale, which contains items assessing the ability to acknowledge suffering in others and being able to put themselves in their position, the Motivation/disposition for helping factor could correspond to the COOL factor “alleviate suffering”, which contain items regarding the efforts of the person aimed at helping others.…”
Section: Discussionmentioning
confidence: 69%
“…Four (4.9%) studies were conducted entirely in India ( Choudhary and Madnawat, 2017a , b ; Singh et al, 2018 ; Prabha and Mittal, 2019 ), two (2.4%) each in Israel ( Eldor, 2018 ; Prabha and Mittal, 2019 ) and Chile ( Brito-Pons et al, 2018 ), and one (1.2%) each in Malaysia ( Owuamalam and Matos, 2019 ) and South Korea ( Moon et al, 2014 ). Eleven (13.4%) additional studies used data from multiple countries, including countries in Western Europe and North America, Israel, Turkey, nine countries in South America ( Chang et al, 2021 ), and Ethiopia, China, and Japan ( Howick et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Patterns for specific countries were inconsistent and inconclusive. Chang et al reported empathy being higher in subjects from South America than Turkey, although scores for alleviating suffering were highest in Turkey and lowest in South America ( Chang et al, 2021 ). Gilbert et al (2017) found that compassion for others was higher in Portugal than in the United States or the United Kingdom.…”
Section: Resultsmentioning
confidence: 99%
“…Turkey is one of the transcontinental countries between Asia and Europe, unifying the Western education system and Anatolian tradition together. Thus, studying compassion within Turkish culture can provide new insights and constructs ( Chang et al, 2021 ). Compassion has also been evaluated from different perspectives such as the evolutionary and social psychology and the spiritual traditions of Buddhism, and Sufism ( Gilbert, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The acquaintance of the Western world with the old Eastern construct “compassion” has continued with abundant research emphasizing its role in wellbeing and its positive effects on mental health, with the inclusion thereof with therapies or intervention programmes ( Barnard and Curry, 2011 ; Özyeşil and Akbağ, 2013 ; Chang et al, 2021 ). Gilbert (2017 , p. 73) defined compassion as a basic algorithm of ‘ sensitivity to suffering in self and others with a commitment to try to alleviate and prevent it .’ Hence first we need to pay attention to and engage with suffering and then second, we need to work out how to be helpful.…”
Section: Introductionmentioning
confidence: 99%